Inter-electrode distance effect on dc discharge characteristics in nitrogen - Lisovskiyс, V.A.; Artushenko, K.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2015)
This paper studies the inter-electrode distance effect on voltage drop across it and cathode sheath thickness. The voltage across the electrodes and the sheath thickness are found to increase when the anode moves away from the cathode through the negative glow. The probe technique reveals that increasing the inter-electrode gap with the current fixed leads to the plasma concentration growth in the negative glow. The discharge current is transported through the negative glow by fast electrons accelerated in the cathode sheath; therefore one requires applying higher voltage across the electrodes to support the current in a longer gap. This is the reason for the increase of the plasma concentration in the negative glow and in the cathode sheath thickness.